Culture, globalization and the world-system : contemporany conditions for the representation of identity - King, Anthony D. (University of the Minnesota Press, 1997)
One of the inaugural books discussing the increasing tendency of cultural practices to cross national boundaries. Updated with a new preface, these influential essays by a distinguished group of cultural critics lay the groundwork for a vital new field of inquiry. Contributors: Barbara Abou-El-Haj, Janet Abu-Lughod, Stuart Hall, Ulf Hannerz, Roland Robertson, John Tagg, Maureen Turim, Immanuel Wallerstein, Janet Wolff.